The quality of mother-infant interactions in Khayelitsha - Sakasa, Pumza Cordelia (Department of Psychology, 2023)
Little research has been done in the developing countries around the issue of postpartum depression and its effects on the face-to-face mother-infant interactions. Murray et at. (1996) conducted a research study of this kind in Britain. Results obtained in the study were used for comparisons with those of the current study, focused on investigating the quality of the face-to-face mother-infant interactions in Khayelitsha, a South African informal settlement. Subjects were derived from two adjoining areas of Khayelitsha that is, SS T and Town II. Recruitments were done using a number of strategies such as visiting the local clinics and hospitals as well as their homes. Permission to do 50 had been negotiated prior the inception of the study. Structured interviews were conducted to screen depressed mothers from the non-depressed. The mental state of thee recruited 147 women was therefore assessed and the quality of their engagement with their infants was determined through videotaped sessions. Analysis of the data was done using Student t tests. The point prevalence rate of DSMIV major depression was found to be 34.7%. Maternal depression was associated with insensitive engagement with the infants as wen as with poor emotional and practical support from the spouse. The rate of depression in Khayelitsha was found to be of major concern for the future of the mothers and their infants. Compared to their British counterparts, the Khayelitsha mothers-infant interactions portrayed more severe disturbances in relation to maternal sensitivity and infant engagement.